THU0177 Prognostic factors of remission in early rheumatoid arthritis (ra). a multiparameter prospective study. (1st June 2001) - Combe, B; Goupille, P; Cantagrel, A; Bozonnat, MC; Sibilia, J; Eliaou, JF; Meyer, O; Sany, J; Daures, JP; Dougados, M
Abstract : Background: Objectives: To determine prognostic factors of remission in early RA. Methods: A cohort of 191 patients with RA and disease duration shorter than 1 year were prospectively followed-up for 3 years. Numerous baseline clinical, laboratory, genetic and radiographic data (Sharp's method modified by van der Heijde) were obtained. Remission, defined by a Disease Activity Score (DAS) < 1.6, was used as outcome measure. 1 Results: Forty eight patients (25.1%) fulfilled the remission criteria at the 3-year follow-up visit. According to Fisher?s exact test, remission was closely related with baseline values of DAS, HAQ score, morning stiffness, tender joint count, C-reactive protein and radiologic scores. No statistically significant correlation was demonstrated for sex, age, extraarticular manifestations, IgM and IgA rheumatoid factors, anti-perinuclear Ab, anti-keratin Ab, anti-HSP 90, anti-calpastatin Ab, antinuclear Ab, YKL-40 and HLA-DRB1* genotypes. The logistic regression analysis revealed that the independent variables able to predict the 3-year remission were: DAS, HAQ score, morning stiffness and total radiographic score. Conclusion: Pronostic factors of remission in early RA were mainly clinical markers of disease activity and radiological scores. Reference: Prevoo, et al . Br J Rheumatol. 1996;35:1101